Pengaruh Perputaran Persediaan, Pertumbuhan Penjualan, Tingkat Harga Pokok Penjualan (HPP), dan Inflasi Terhadap Profitabilitas PT. Perikanan Nusantara (Persero) Cabang Benoa Tahun 2016-2018 - Arta, Komang Susila; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to analyze how profitability is affected by inventory turnover, sales growth, COGS levels, and inflation. This research includes quantitative research that uses statistical data analysis, such as normality, autocorrelation, multicollinearity, and heteroscedasticity tests which include the classical assumption test and multiple linear regression analysis consisting of the t test and the coefficient of determination (R2) test. The place to do this research is: PT. Perikanan Nusantara (Persero) Branch of Benoa. The study population of 36 months was taken from the monthly financial statements. From the research that has been done, it gives the following results; 1). Inventory turnover has a positive and significant effect on profitability of 48.9%, 2). Sales growth has a positive and significant effect on profitability of 39.2%. 3). The level of COGS has a positive and significant effect on profitability of 69.2%. 4). Inflation has no effect on profitability of 0%. 5). Inventory turnover, sales growth, COGS levels and inflation simultaneously have a positive and significant effect of 94.9% at PT. Perikanan Nusantara (Persero) Branch of Benoa in 2016-2018.